Condition Assessment Concepts and their Role in Facilitating Sustainable Range Management - Gibson, R S; Allen, W J; Bosch, O J.H (Annals of Arid Zone, 2016)
This paper reviews the development of the theories and concepts underpinning current understanding of vegetation dynamics in the world’s rangelands. The influence these have had on the development of condition assessment techniques is also demonstrated. Unless they are placed in a context where they can aid decision-making, however, the results of monitoring have little meaning or use. The paper concludes by describing how monitoring techniques can be integrated into systems-oriented and community-based research to make maximum use of the information necessary for sustainable rangeland decisions.